The giving tree - Silverstein, Shel. (New York : HarperCollins, 1964)
A young boy grows to manhood and old age experiencing the love and generosity of a tree which gives to him without thought of return.
Book Links (A.L.A.).
Book Report.
Horn Book.
2.9
K-3
Keywords: Generosity -- Fiction; Love -- Fiction; Trees -- Fiction; Generosity -- Fiction; Love -- Fiction; Trees -- Fiction